Five recommendations for software evolvability. Issue 9 (15th March 2018) - Rajlich, Václav
Abstract: Evolvability of software lies in intersection of 3 factors: evolving system properties, human factors present in the developer team, and evolution demands. The paper presents 5 recommendations that enhance software evolvability: defined processes of software change, distinction between evolving and stabilized part of the code, analyzable code segments, significant concept encapsulation, and avoidance of wrapping.